Familial clustering of dysbiotic oral and fecal microbiomes in juvenile dermatomyositis - Koester, Sean T.; Chow, Albert; Pepper-Tunick, Evan; Lee, Peggy; Eckert, Mary; Brenchley, Laurie; Gardner, Pamela; Song, Hyun Jung; Li, Naisi; Schiffenbauer, Adam; Volochayev, Rita; Bayat, Nastaran; et al. (Scientific reports, 2024)
Juvenile dermatomyositis (JDM) is a rare immune-mediated disease of childhood with putative links to microbial exposures. In this multi-center, prospective, observational cohort study, we evaluated whether JDM is associated with discrete oral and gut microbiome signatures. We generated 16S rRNA sequencing data from fecal, saliva, supragingival, and subgingival plaque samples from JDM probands ( n = 28). To control for genetic and environmental determinants of microbiome community structure, we also profiled microbiomes of unaffected family members ( n = 27 siblings, n = 26 mothers, and n = 17 fathers). Sample type (oral-vs-fecal) and nuclear family unit were the predominant variables explaining variance in microbiome diversity, more so than having a diagnosis of JDM. The oral and gut microbiomes of JDM probands were more similar to their own unaffected siblings than they were to the microbiomes of other JDM probands. In a sibling-paired within-family analysis, several potentially immunomodulatory bacterial taxa were differentially abundant in the microbiomes of JDM probands compared to their unaffected siblings, including Faecalibacterium (gut) and Streptococcus (oral cavity). While microbiome features of JDM are often shared by unaffected family members, the loss or gain of specific fecal and oral bacteria may play a role in disease pathogenesis or be secondary to immune dysfunction in susceptible individuals.